Between Technological Determinism and Social Construction: The Adoption of Smartphones in the Samin Community of Sukolilo, Central Java - Angela Atik Setiyanti; Rini Darmastuti; Titi Susilowati Prabawa; Johanes Mardimin (SISFORMA, 2026)
The rapid expansion of digital technologies has intensified debates on whether technological change is primarily driven by technological determinism or shaped through social and cultural processes. While smartphones have become central to digital transformation, existing studies often assume linear and uniform patterns of adoption, overlooking the role of local socio-cultural contexts. This study addresses this gap by examining how smartphones are adopted within the Samin community of Sukolilo, Central Java—an indigenous community characterized by strong moral values and non-formal learning practices. Using a qualitative ethnographic approach, data were collected through observation, interviews, and focus group discussions. The findings show that smartphone adoption is selective, socially regulated, and negotiated through the interaction between technological affordances, socio-cultural values, and everyday practices. The study proposes the Negotiated Smartphone Adoption Model, contributing to ICT4D and technology-society discourse.